CSF‐1R inhibition disrupts the dialog between leukaemia cells and macrophages and delays leukaemia progression. Issue 22 (10th October 2020) - Li, Kun; Xu, Wenfu; Lu, Ke; Wen, Yuxi; Xin, Tianqing; Shen, Yaqing; Lv, Xueyan; Hu, Shimin; Jin, Runming; Wu, Xiaoyan
Abstract: Research in the last few years has revealed that leukaemic cells can remodel the bone marrow niche into a permissive environment favouring leukaemic stem cell expansion. Tumour‐associated macrophages (TAMs) are prominent components of the tumour microenvironment and play an important role in the onset and progression of solid tumours. However, little is known about their role in the development of acute lymphoblastic leukaemia (ALL). Using a unique mouse model of T‐ALL induced by injection of EL4 T‐cell lymphoma cells to syngeneic C57BL/6 mice, we report herein that ALL leads to the invasion of leukaemia‐associated monocyte‐derived cells (LAMs) into the bone marrow and spleen of T‐ALL mice. Furthermore, we found that leukaemia cells could polarize bone marrow–derived macrophages (BMDMs) into LAMs. In turn, LAMs were able to protect leukaemia cells from drug‐induced apoptosis in vitro. Therapies targeted against the TAMs by inhibiting colony stimulating factor‐1 receptor (CSF‐1R) have emerged as a promising approach for cancer treatment. In this study, we demonstrate that CSF‐1R inhibition inhibits the viability of BMDMs, blocks LAMs polarization and reduces the abundance of LAMs in T‐ALL mice. In vivo, combination treatment of CSF‐1R inhibitor and vincristine (VCR) dramatically increased the survival of T‐ALL mice and delayed leukaemia progression compared with VCR monotherapy. Finally, these data reinforce the role of microenvironments in leukaemia and suggest that macrophages are a potential target for the development of novel therapeutic strategies in T‐ALL.